Gaya bahasa repetisi ustaz adi hidayat tentang penyelenggaran ibadah dalam wabah covid-19 - Luthfi Luthfi; Rahmad Nuthihar; Herman RN; Wahdaniah Wahdaniah (BAHASTRA, 2020)
This study examines the style of repetition in Ustaz Adi Hidayat's preach (UAH) related to the socialization of the fatwa of the Indonesian Council of Religious Scholars (MUI) about performing worship during the COVID-19 outbreak. Data of this study were taken from the UAH's lecture which aired via Official Adi Hidayat Youtube account. Data analysis was carried out by transcribing the sermon, marking the information containing repetition and making analyzes. The results of this study conclude that not all forms of repetition styles are presented in UAH's preach, such as epistrophe.Â  The styles of repetition contained in his preach consist of (1) epizeuxis, (2) tautotes, (3) anaphora, (4) symploce, (5) mesodiplosis, (6) epanalepsis, (7) anadiplosis. Besides, the finding also reveals the existence of two repetition styles in one data, namely (1) anaphora and tautotes, (2) epizeuxis and tautotes, and (3) anaphora and mesodiplosis. The styles of repetition used by UAH aim to emphasize the key points of the MUI fatwa so that it can be easily understood by audiences. It is proven by the dominance of the epizeuxis and tautotes style found in this study. The findings of repetition style in spoken discourse will be different from that of written discourse. The repetition style in spoken is spontaneous. Preachers generally develop their style until repetition becomes their characteristic.